Ventilatory and physiological responses in swimmers below and above their maximal lactate steady state - Espada, M. C.; Reis, J. F.; Almeida, T. F.; Bruno, P. M.; Vleck, V. E.; Alves, F. B. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to understand the ventilatory and physiological responses immediately below and above the maximal lactate steady-state (MLSS) velocity and to determine the relationship of oxygen uptake (VO2) kinetics parameters with performance, in swimmers. Competitive athletes (N = 12) completed in random order and on different days a 400-m all-out test, an incremental step test comprising 5 × 250- and 1 × 200-m stages and 30 minutes at a constant swimming velocity (SV) at 87.5, 90, and 92.5% of the maximal aerobic velocity for MLSS velocity (MLSSv) determination. Two square-wave transitions of 500 m, 2.5% above and below the MLSSv were completed to determine VO2 on-kinetics. End-exercise VO2 at 97.5 and 102.5% of MLSSv represented, respectively, 81 and 97% of VO2max; the latter was not significantly different from maximal VO2 (VO2max). The VO2 at MLSSv (49.3 ± 9.2 ml/kg/min) was not significantly different from the second ventilatory threshold (VT2) (51.3 ± 7.6 ml/kg/min). The velocity associated with MLSS seems to be accurately estimated by the SV at VT2 (vVT2), and vVO2max also seems to be estimated with accuracy from the central 300-m mean velocity of a 400-m trial, indicators that represent a helpful tool for coaches. The 400-m swimming performance (T400) was correlated with the time constant of the primary phase VO2 kinetics (tp) at 97.5% MLSSv, and T800 was correlated with tp in both 97.5 and 102.5% of MLSSv. The assessment of the VO2 kinetics in swimming can help coaches to build training sets according to a swimmer`s individual physiological response.